The machineries, regulation and cellular functions of mitochondrial calcium. Issue 11 (November 2018) - Giorgi, Carlotta; Marchi, Saverio; Pinton, Paolo
Abstract Calcium ions (Ca2+ ) are some of the most versatile signalling molecules, and they have many physiological functions, prominently including muscle contraction, neuronal excitability, cell migration and cell growth. By sequestering and releasing Ca2+, mitochondria serve as important regulators of cellular Ca2+ . Mitochondrial Ca2+ also has other important functions, such as regulation of mitochondrial metabolism, ATP production and cell death. In recent years, identification of the molecular machinery regulating mitochondrial Ca2+ accumulation and efflux has expanded the number of (patho)physiological conditions that rely on mitochondrial Ca2+ homeostasis. Thus, expanding the understanding of the mechanisms of mitochondrial Ca2+ regulation and function in different cell types is an important task in biomedical research, which offers the possibility of targeting mitochondrial Ca2+ machinery for the treatment of several disorders. Uptake of Ca2+ ions by mitochondria regulates their functions and serves to buffer Ca2+ concentrations to maintain cellular Ca2+ homeostasis. Better understanding of the mechanisms, regulation and (patho)physiology of mitochondrial Ca2+ influx and efflux offers the possibility to target mitochondrial Ca2+ machineries for therapeutic benefit.